Bamboo fibre reinforced composite structures and their mechanical properties - (:unkn) unknown (My University, 2009)
Generally felt and woven fabrics are used as a reinforcement component of fibre in composite structures. Glass and carbon fibres are the most widely used materials in multiaxial fabrics to increase the mechanical properties of reinforced composites. in this study, it has been aimed to study the natural fibres to observe the mechanical properties of the composite structures that are produced. For this purpose bamboo fibres are used, instead of glass and carbon. The research was carried out with the Nm 0.93 bamboo slivers by using vinyl ester resin at different reinforcement ratios to produce the hand lay-up composite structures. The produced reinforced composite samples were then tested for their three point bending and tensile strength tests. The fracture surfaces of the tensile strength samples and three point bending samples were also inspected on the scanning electron microscope. According to the results, it has been evaluated that bamboo fibres with 3mm fibre length and above increases the mechanical properties of composite structures. As a result, the produced bamboo fibre reinforced composite structures have presented good mechanical properties.
Keywords: Bamboo sliver; Fracture surface; Hand lay-up method; Mechanical properties; Reinforced composite